(untitled) (Training and Practice : Journal of Educational Sciences, 2022)
The first really big decision in the course of life, which presupposes sufficient maturity, is the question of choosing a career after leaving secondary school. (The role of parents is typically emphasised in the career choice process after graduating from elementary school, due to the immaturity of students,) Service-learning centres (hereinafter referred to as ’SLC’) offer an excellent opportunity to prepare for this, and their stated aims include not only the development and sensitisation of students’ social skills but also support for career guidance. All the experience gained in this context shows that this topic is undeservedly neglected. In this study, we are trying to show, through a few examples, how to approach SLC from its guidance aspect and make use of the opportunities that are often left unexploited in the programme.